6600 years of earthquake record in the Julian Alps (Lake Bohinj, Slovenia). Issue 5 (25th March 2018) - Rapuc, William; Sabatier, Pierre; Andrič, Maja; Crouzet, Christian; Arnaud, Fabien; Chapron, Emmanuel; Šmuc, Andrej; Develle, Anne‐Lise; Wilhelm, Bruno; Demory, François; Reyss, Jean‐Louis; Régnier, Edouard; et al.
Abstract: Sequences of lake sediments often form long and continuous records that may be sensitive recorders of seismic shaking. A multi‐proxy analysis of Lake Bohinj sediments associated with a well‐constrained chronology was conducted to reconstruct Holocene seismic activity in the Julian Alps (Slovenia). A seismic reflection survey and sedimentological analyses identified 29 homogenite‐type deposits related to mass‐wasting deposits. The most recent homogenites can be linked to historical regional earthquakes (i.e. 1348 ad, 1511 ad and 1690 ad ) with strong epicentral intensity [greater than 'damaging' (VIII) on the Medvedev–Sponheuer–Karnik scale]. The correlation between the historical earthquake data set and the homogenites identified in a core isolated from local stream inputs, allows interpretation of all similar deposits as earthquake related. This work extends the earthquake chronicle of the last 6600 years in this area with a total of 29 events recorded. The early Holocene sedimentary record is disturbed by a seismic event (6617 ± 94 cal yr bp ) that reworked previously deposited sediment and led to a thick sediment deposit identified in the seismic survey. The period between 3500 cal yr bp and 2000 cal yr bp is characterized by a major destabilization in the watershed by human activities that led to increases in erosion and sedimentation rates. This change increased the lake's sensitivity to recording an earthquake (earthquake‐sensitivity threshold index) with the occurrence of 72 turbidite‐type deposits over this period. The high turbidite frequency identified could be the consequence of this change in lake earthquake sensitivity and thus these turbidites could be triggered by earthquake shaking, as other origins are discarded. This study illustrates why it is not acceptable to propose a return period for seismic activity recorded in lake sediment if the sedimentation rate varies significantly.